Airborne Ultrafine Particle and Acute Physiological Effects during Maximal Aerobic Power Test - Angelo Rodio; Francesco Misiti; Alessandro Zagaglia; Luca Stabile; Giorgio Buonanno; Luigi Fattorini (Aerosol and Air Quality Research)
Abstract Background The practice of physical exercise in polluted areas could lead to adverse health effects that may contribute to the incidence and/or worsening of respiratory and cardiovascular diseases and some types of cancer. Methods Male recreational cyclists performed tests in a manner randomized crossover in two environmental conditions: low (environmental noise exposure) and high ultrafine particle concentration. For each trial, oxygen consumption (VO2), carbon dioxide production (VĊO2), respiratory frequency (Rf), tidal volume (Vt), pulmonary ventilation (VE), and mechanical workload (WL) were measured. Gross efficiency (GE) was determined using the ratio between mechanical power output and metabolic power input. Repeated-measures ANOVA was applied to evaluate differences (P < 0.05) between physiological and mechanical parameters and compare oxygen consumption trends in the two scenarios. RESULTS: HR, Rf, and VE values do not show any significant difference. On the contrary, VO2peak increased (P < 0.05) under high exposure (41.6 ± 4.31 mL kg–1 min–1), during high-intensity exercise, compared to a low exposure (38.4 ± 4.05 mL kg–1 min–1). VO2 and GE show differences (p < 0.05) between low and high ultrafine particle concentration conditions during exercise above 80% WLpeak. Conclusions Present data suggest that high airborne UFPs levels impair recreational cyclists’ gross efficiency.